Hypoxic brain damage after intramuscular self-injection of diclofenac for acute back pain - Schäbitz, Wolf-Rüdiger; Berger, Christian; Knauth, Michael; Meinck, Hans-Michael; Steiner, Thorsten (European journal of anaesthesiology, 2001)
We present a case of hypoxic brain damage that occurred after intramuscular injection of diclofenac due to a severe anaphylactic reaction. A 38-year-old nurse treated herself for acute lower back pain with 100 mg diclofenac intramuscularly. Five minutes later, she collapsed and developed coma and respiratory arrest. After cardiopulmonary resuscitation she was transferred to hospital. On admission she was comatose and received controlled ventilation of the lungs. Magnetic resonance imaging and computerized tomography showed signs of hypoxic brain injury and the patient died from central cardiopulmonary failure 7 days later. Intramuscular treatment with non-steroidal anti-inflammatory drugs such as diclofenac has rare but potentially severe side-effects. Therefore, intramuscular injections are inappropriate and should be replaced with oral or rectal treatment, which has similar absorption profiles.